Enhanced thermal energy storage based on phase change materials with enhanced structures - Sek, Mun Pin (Nanyang Technological University, 2021)
In almost all industrial processes, more than half of the input energy is turned into waste heat. One method to better harness thermal energy involves storing the waste heat energy using thermal energy storage devices filled with Phase Change Materials (PCMs). This study aims to characterise melting of PCM in a plain structure, fan-finned, tree-finned, and topology-optimised structure heat sinks at different power inputs. This study compared the topology-optimised heat sink for natural convection against another topology-optimised heat sink (tree-finned) that natural convection was not considered. The two heat sinks were also compared to a conventional fin-shaped heat sink to see the improvement in their thermal performance. In all experiments, both topology-optimised heat sinks were able to maintain lower base temperatures compared to the fan-finned and plain structure. The tree-structure performed slightly better at 48 W while the newly designed TO structure performed better at 27 W. This suggests that the topology-optimised heat sink is a more efficient cooling device as compared to the fin-shaped heat sink.